Cervical epidural abscess caused by brucellosis - Lampropoulos, Christos (BMJ Case Rep, 2012)
A 70-year-old Greek lady presented with fever, arthralgias of knees, cervical and lumbar pain during the last month. On clinical examination the patient was found to have tenderness of the cervical and the lumbar spine with great motion restriction. The blood tests revealed high erythrocyte sedimentation rate and C-reactive protein, abnormal liver function tests and a positive rheumatoid factor. Serological test for Brucella was positive while cervical MRI revealed epidural abscess and spondylodiscitis. Conservative treatment with streptomycin (it was substituted by rifampicin after the third week) and doxycyclin for 4 months significantly improved her symptoms. The frequency as well as the diagnosis and management of this manifestation are discussed.